IMPLEMENTASI AJARAN TRI N DALAM MENGEMBANGKAN KREATIVITAS SISWA PADA PEMBUATAN KARYA SENI BATIK DI SEKOLAH DASAR - Rista Dwi Susanti; Moh Rusnoto Susanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Primary education plays a very important role in developing students' creative attitudes. One alternative that can be done to foster creativity is by implementing the Tri N teachings (niteni, niroake, nambahake) in the learning process. Tri N is one of the Tamansiswa teachings used by Ki Hadjar Dewantara in the educational process. This article aims to present the implementation of Ki Hadjar Dewantara's Tri N teachings to enhance student creativity through the creation of batik artwork in elementary schools. This type of research is Qualitative Descriptive research. Data collection techniques were carried out using observation, creative attitude observation rubrics, interviews, and documentation. The results of the study show that by implementing the Tri N teachings, students develop creativity that enables them to produce innovative batik art.